Diatesis Pasif Bahasa Jepang - Astami, Timur Sri (Lingua Cultura, 2008)
Article represents passive diathesis which is one of many kinds and function of grammatical analysis. Passive diathesis or mostly known as passive voice is usually used to show a relation between the speaker and his view on something. In Japanese, passive diathesis is divided in three parts such as, kihon teki na ukemi (basic passive voice), mochi mushi ukemi (belonging passive voice), higai no ukemi (loss passive voice), and hijou no ukemi (neutral passive voice). Each passive voice in Japanese has different function and meaning, therefore in teaching Japanese language it should take more exercise and example in order to be more complete and comprehensive.